IMPLEMENTASI METODE TAKRIR DALAM PEMBELAJARAN QIRA'AH SAB'AH - Sufyan Hamid; Ahmad Bashori (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
The Takrir method is an effective method in teaching Qira'ah Sab'ah. This method involves interactions between students and teachers through group discussions that can significantly improve students' ability in reading Qira'ah Sab'ah. This research discusses the implementation of the Takrir method as one of the learning methods in studying Qira'ah Sab'ah at Pondok Pesantren Tahfizul Qur'an Al-Hasan Ponorogo. This research uses a qualitative approach to explore in-depth information through observation, interviews, and document analysis. The purpose of this study is to understand the process of implementing the Takrir method in the learning of Qira'ah Sab'ah at Pondok Pesantren Tahfizul Qur'an Al-Hasan and its impact on students' learning outcomes. The results of the study indicate that the implementation of the Takrir method can increase students' motivation and interest in learning, as well as facilitate their understanding and pronunciation of Qira'ah Sab'ah. Additionally, the Takrir method can also improve students' speaking skills and self-confidence in presenting their learning outcomes. In conclusion, this research recommends the consistent and planned implementation of the Takrir method in the learning of Qira'ah Sab'ah at the pesantren. Furthermore, further research is needed to more accurately measure the impact of implementing the Takrir method in the learning of Qira'ah Sab'ah.